DNA methylation and hydroxymethylation patterns in acute myeloid leukemia patients with mutations in DNMT3A and IDH1/2 and their combinations - Šestáková, Šárka; Krejčík, Zdeněk; Folta, Adam; Cerovská, Ela; Šálek, Cyril; Merkerová, Michaela Dostálová; Pecherková, Pavla; Ráčil, Zdeněk; Mayer, Jiří; Cetkovský, Petr; Remešová, Hana (Cancer biomarkers, 2019)
BACKGROUND: Aberrant epigenetic patterns are a hallmark of acute myeloid leukemia (AML). Mutations in profound epigenetic regulators DNMT3A and IDH1/2 often occur concurrently in AML. OBJECTIVES: The aim was to analyze DNA methylation, hydroxymethylation and mRNA expression profiles in AML with mutations in DNMT3A and IDH1/2 (individually and in combinations). METHODS: Infinium MethylationEPIC BeadChip (Illumina) covering 850,000 CpGs was utilized. The validation of hydroxy-/methylation data was done by pyrosequencing. HumanHT-12 v4 Expression BeadChip (Illumina) was used for expression examination. RESULTS: Hierarchical clustering analysis of DNA hydroxy-/methylation data revealed clusters corresponding to DNMT3A and IDH1/2 mutations and CD34+ healthy controls. Samples with concurrent presence of DNMT3A and IDH1/2 mutations displayed mixed DNA hydroxy-/methylation profile with preferential clustering to healthy controls. Numbers and levels of DNA hydroxymethylation were low. Uniformly hypermethylated loci in AML patients with IDH1/2 mutations were enriched for immune response and apoptosis related genes, among which hypermethylation of granzyme B (GZMB) was found to be associated with inferior overall survival of AML patients (P= 0.035). CONCLUSIONS: Distinct molecular background results in specific DNA hydroxy-/methylation profiles in AML. Site-specific DNA hydroxymethylation changes are much less frequent in AML pathogenesis compared to DNA methylation. Methylation levels of enhancer located upstream GZMB gene might contribute to AML prognostication models.
Keywords: senioři; CHFR; Granzymes; isocitrátdehydrogenasa; Gene Expression Profiling; senioři nad 80 let; Leukocytes, Mononuclear; Prognosis; leukocyty mononukleární; Isocitrate Dehydrogenase; Middle Aged; DNMT3A and IDH1/2 mutations; mužské pohlaví; mutace; DNA Methyltransferase 3A; Leukemia, Myeloid, Acute; DNA methyltransferasa 3A; AML; Aged, 80 and over; granzymy; ženské pohlaví; prognóza; Mutation; hydroxymethylation; DNA-(cytosin-5-)methyltransferasa; Humans; metylace DNA; DNA (Cytosine-5-)-Methyltransferases; methylation; lidé středního věku; akutní myeloidní leukemie; DNA Methylation; stanovení celkové genové exprese; GZMB; Female; Aged; lidé; Male